Configuring the evolving role of ewom on the consumers information adoption - Muddasar Ghani Khwaja; Umer Zaman (Journal of Open Innovation: Technology, Market, and Complexity, 2020)
Electronic word-of-mouth (eWOM) is reckoned to be one of the underlying factors that augments online retailing. The information adoption protocols have been revamped due to the extensive online information; consequently, adding a significant influence on the online purchase behaviors. Consumer review websites, shopping platforms, blogs and discussion forums are some of the leading eWOM platforms, as emphasized in prior literature. The current study, however, focuses on eWOM on the social media platforms, as the consumers' online decision-making process is confined to the adoption of information in the first phase. The study examines the effects of the antecedents of eWOM and multiple mediators (i.e. perceived risk, argument quality, information usefulness and trust inclination) on the consumers information adoption. The study used survey-based data and structural equation modelling (SEM) technique to determine the causality among the constructs. Future directions provide concrete managerial and theoretical implications as highlighted in the study.
Keywords: 650; eWOM; information adoption; perceived risk; source credibility; trust inclination